Arterial Catheterization and Infection: Toll‐like Receptors in Defense against Microorganisms and Therapeutic Implications. Issue 6 (14th August 2015) - Hambsch, Zakary J.; Kerfeld, Mitchell J.; Kirkpatrick, Daniel R.; McEntire, Dan M.; Reisbig, Mark D.; Youngblood, Charles F.; Agrawal, Devendra K.
Abstract: Radial artery catheterization has become a preferred route over femoral artery catheterization, in order to monitor the blood pressure of hemodynamically unstable patients or for repeated sampling of arterial blood gases. While the incidence of catheter‐related infection is lower in the radial artery than the femoral artery, infection remains a major issue that requires attention. In this review of the literature, we discuss infectious complications of radial artery catheterization, with a focus on various risk factors and establishing the most common causative agents. We also critically review the role of the innate immune system involving Toll‐like receptors (TLRs) in host‐defense, with the goal of establishing a common pathway used by the innate immune system via TLRs to combat the pathogens that most commonly cause infection in radial artery catheterization. If this pathway can be therapeutically manipulated to preemptively attack pathogenic agents, immunomodulation may be an option in reducing the incidence of infection in this procedure.